Police brutality: a Philadelphia story - Williams, Ife (Policing perspectives and challenges in the twenty-first century, 2023)
"Using Philadelphia as a case study, this book analyzes the evolution of predatory policing, attempts to curb aggressive practices, and the resultant chasm between reform efforts and the expansion of police discretion"--